Development and validation of a fast sub-channel code for LWR multi-physics analyses - Chaudri, Khurrum Saleem; Kim, Jaeha; Kim, Yonghee (Nuclear engineering and technology, 2019)
A sub-channel solver, named Steady and Transient Analyzer for Reactor Thermal hydraulics (START), has been developed using the homogenous model for two-phase conditions of light water reactors. The code is developed as a fast and accurate TH-solver for coupled and multi-physics calculations. START has been validated against the NUPEC PWR Sub-channel and Bundle Test (PSBT) database. Tests like single-channel quality and void-fraction for steady state, outlet fluid temperature for steady state, rod-bundle quality and void-fraction for both steady state and transient conditions have been analyzed and compared with experimental values. Results reveal a good accuracy of solution for both steady state and transient scenarios. Axially different values for turbulent mixing coefficient are used based on different grid-spacer types. This provides better results as compared to using a single value of turbulent mixing coefficient. Code-to-code evaluation of PSBT results by the START code compares well with other industrial codes. The START code has been parallelized with the OpenMP algorithm and its numerical performance is evaluated with a large whole PWR core. Scaling study of START shows a good parallel performance. Keywords: Sub-channel, LWR, PSBT, Thermal hydraulics, Multi-physics analyses, START